Global governance in the age of digital risks: chinese initiative for artificial intelligence - Stekić, Nenad (Sociološki pregled, 2025)
The paper analyzes China’s newly-proposed initiatives in the sphere of artificial intelligence (AI) governance and the development of digital infrastructure, with a focus on the Global AI Governance Initiative and Digital Silk Road Initiative. Through the analysis of political documents, government statements and existing literature, the paper examines manners in which China positions itself as a leader in AI governance, while simultaneously spreading its digital impact at the global level. China’s dual approach – promoting the AI governance framework and construction of digital infrastructure abroad – is claimed to enable China to form international norms and standards related to new technologies. However, this strategy causes concerns in terms of digital authoritarianism, technological dependence and privacy issues. By examining the interaction between Chinese national and international digital policies, this research contributes to understanding AI geopolitical implications and digital technologies.
Keywords: artificial intelligence; digital infrastructure; global initiative; Digital Silk Road; China